Analisis Tingkat Kepatuhan BPJS Kesehatan terhadap Fatwa DSN MUI dalam Pengelolaan Dana: Studi di Kantor BPJS Kesehatan Cabang Lubuk Pakam - Maulana Ahmad Abadi; Irham Dongoran (CV Global Research Publication, 2026)
This study aims to analyze the level of compliance of BPJS Kesehatan with the Fatwa of the National Sharia Council-Indonesian Council of Ulama (DSN-MUI) No. 98/DSN-MUI/XII/2015 concerning the Guidelines for the Implementation of Sharia-Based National Health Insurance, particularly in the aspects of fund management and institutional operations. This research employed a qualitative case study approach at the Lubuk Pakam Branch of BPJS Kesehatan. Data were collected through observation, in-depth interviews, document analysis, and literature review, and were analyzed using descriptive qualitative techniques with the DSN-MUI Fatwa as the analytical framework. The findings indicate that BPJS Kesehatan has implemented several Sharia principles, including ta‘āwun (mutual assistance), the separation of Social Security Fund assets from operational assets, financial transparency, and participant-oriented fund management. Nevertheless, compliance with the DSN-MUI Fatwa remains partial. The institution has not established a Sharia Supervisory Board, the Fatwa functions merely as a policy consideration rather than an operational guideline, and several aspects of the National Health Insurance scheme continue to raise concerns from the perspective of Islamic law, particularly regarding the potential presence of gharar (uncertainty), maysir (gambling), and riba (usury). The study concludes that although BPJS Kesehatan substantively reflects several Islamic values in its governance, full compliance with the DSN-MUI Fatwa has not yet been achieved. Therefore, greater regulatory harmonization, strengthened Sharia governance, and enhanced supervisory mechanisms are required to develop a national health insurance system that is more consistent with the principles of Islamic law.